SAT0041 Microrna-146A An Important Regulator of Local Bone Destruction in Inflammatory Arthritis. (15th July 2016) - Saferding, V.; Puchner, A.; Goncalves-Alves, E.; Hofmann, M.; Hayer, S.; Georgel, P.; Koenders, M.M.; Schabbauer, G.; Smolen, J.S.; Steiner, G.; Redlich, K.; Blüml, S.
Abstract : Background: MicroRNA (MiR-) 146a plays an important role in the regulation of the innate immune response and has also been shown to suppress cancer development in myeloid cells. Although in late stages of arthritis elevated expression of miR-146a in synovial tissue of rheumatoid arthritis patients was detected, the level of this miRNA was found to be down regulated in early disease, but its role in the development of inflammatory arthritis is still elusive. Objectives: To analyse the role of miR-146a in arthritis using two different disease models hTNFtg and K/BxN serum transfer arthritis and the regulatory function of this miRNA in fibroblasts and immune cells. Methods: We induced K/BxN serum transfer arthritis in wild type and miR-146a –/– mice. As a second inflammatory arthritis model we crossed miR-146a deficient into hTNFtg mice. Disease severity was assessed clinically and histologically in both arthritis disease models. Blood of arthritis animals was analysed by flow cytometry. Serum cytokine levels were measured by Elisa. RNA expression levels were measured by qPCR. Proliferation of fibroblasts was analysed histologically and by 3 [H]thymidine incorporation. Results: Absence of miR-146a leads to increased clinical signs of the induced serum transfer arthritis. In line, higher serum levels of the proinflammatory cytokines IL-12 and IL-6 were measured in miR-146a deficient compared to wt mice. When we crossed miR-146a –/– into hTNFtg mice, histological examination revealed a significant increase in synovial inflammation and even more striking a more than twofold increase in local bone destruction due to increased generation of osteoclasts in the tarsal joints in miR-146a –/– /hTNFtg mice compared to hTNFtg mice. Interestingly, systemic bone loss was comparable in hTNFtg compared to miR-146a –/– /hTNFtg mice, suggesting an important local role of miR-146a. Indeed, we detected increased levels of IL-1β, TRAF6 and RANKL and decreased expression of OPG locally in the paws of miR-146a –/– /hTNFtg compared to hTNFtg mice. Analysing the content of myeloid cells in the blood of arthritis diseased mice, revealed significantly increased numbers of circulating CD11b + as well as CD11c + cells in mice lacking miR-146a. Bone marrow transplants demonstrated a pivotal role for miR-146a in mesenchymal cells in controlling local osteoclast generation and bone destruction. Moreover loss of miR-146a leads to enhanced proliferation of synovial fibroblasts in vitro and in vivo . Conclusions: These data demonstrate an important mitigating role of the miR-146a in inflammatory arthritis, most importantly in local bone destruction, by controlling mesenchymal expression of osteoclastogenic factors. This shows an important anti-inflammatory role of miR-146a, which might possibly be exploited for therapeutic purposes. Disclosure of Interest: None declared